Answer:
f(29) = -
![(9)/(290)](https://img.qammunity.org/2021/formulas/mathematics/high-school/4br01tv6kqhhodmrat0nrdqdl0lpetdwxp.png)
Explanation:
Step 1: substitute f(29) into the equation.
f(29) = 2(29 - 20)²⁻³
29 replaces x.
Step 2: simplify the exponent
f(29) = 2(29 - 20)⁻¹
2-3 is -1, so the exponent is -1
Step 3: distribute the exponent to the parentheses
f(29) = 2(
-
)
Since the exponent is a negative one, basically make it a fraction with the base as the denominator and the exponent as a numerator. I don't know too much about negative exponents, but this is how to factor in a -1.
Step 4: Distribute.
f(29) =
![(2)/(29) -(2)/(20)](https://img.qammunity.org/2021/formulas/mathematics/high-school/u0bzv5dec0m875ojv89tiwmisi8u0e3ehh.png)
Step 5: Simplify before finding a common denominator (2/20 cancels out)
f(29) = 2/29 - 1/10
Step 6: Find a common denominator (290)
f(29) =
-
![(29)/(290)](https://img.qammunity.org/2021/formulas/mathematics/high-school/r9mkgl3z63yosiwvgqxbbpijhqpndde8gw.png)
Step 7: Simplify
f(29) = -
![(9)/(290)](https://img.qammunity.org/2021/formulas/mathematics/high-school/4br01tv6kqhhodmrat0nrdqdl0lpetdwxp.png)
TBH I'm not sure this is correct, but I hope this helps =)